SPELLING BEE IN TEACHING VOCABULARY - Anisa Rohmawati (Journal of English and Education, 2015)
The study entitled “Spelling Bee in Teaching Vocabulary” discovers the effectiveness of the use of Spelling Bee in teaching vocabulary using descriptive text and discovers students’ perceptions toward the Spelling Bee game. The study implements a pre-experimental design. The sample consists of 26 students of seventh grade students of one of Junior High School in Cimahi. The sample is given Spelling Bee treatment that was adopted from Stone (2010). The data of this study are obtained through a post-test and questionnaire. The post-test is given in the form of spelling test. The data from the post-test are analyzed statistically using SPSS 20 for Windows. The result shows that the lowest score on the post-test is 61.00. Meanwhile, the highest score is an excellent score, 100. Then, the mean score is 86.85. From the result, it can be concluded that Spelling Bee is effective to be implemented in English vocabulary learning since nearly all of the students know and are able to spell the words correctly. Meanwhile, the data from the questionnaire shows that 99.24% of the students agree that Spelling Bee gives positive impact to students’ vocabulary learning. In contrary, only 0.76% of students give negative perception toward Spelling Bee. Spelling Bee is highly recommended to be implemented in English classrooms since it is good for students. Through Spelling Bee, students can practice their spelling skill and create a fun atmosphere in the classroom.